Methylphenidate transdermal system: clinical applications for attention-deficit/hyperactivity disorder. Issue 3 (May 2011) - Elia, Josephine; Wilson, Zoe; La Porta, Lilly Sehgal; Algon, Sibel A; Prowler, Matthew L; Cartwright, Shanique T; McKenna, Patricia A; Laracy, Seth; Takeda, Toshinobu; Borgmann-Winter, Karin
The methylphenidate transdermal system (MTS) provides a novel method of delivery for methylphenidate, a well-studied and effective medication for attention-deficit/hyperactivity disorder. The MTS achieves two major goals. First, the delivery system allows for administration throughout the day with a single patch, thus improving adherence. Second, it is the first approved attention-deficit/hyperactivity disorder medication that is not administered orally, thus bypassing gastrointestinal absorption and first-pass metabolism through the enteric circulation. In this article, we review the current data on MTS, including preclinical, clinical and post-marketing studies, and compare efficacy and tolerability to currently available treatments.